Noise Levels from selected religious centres and perceived non-auditory health effects experienced by residents in Owo Town, Ondo State, Nigeria (2015)
In recent times urban noise pollution has grown in magnitude and scope causing palpable effects on public life. Whereas studies have shown the pattern of noise pollution from traffic and industrial sources, little is known about noise from religious settings. We determined the noise levels and then assessed its non-auditory effects on residents. Twelve religious centers: Islamic worship centres (IWC) and Christian worship centres (CWC) were purposively selected based on potential noise generation capacities. Noise level measurements from the religious centers were taken at three timesofthe day (5-8am, l lam-2pmand5-8pm) using AEMC sound meter for 8 consecutive weeks. Values obtained were compared with WHO guidelines limit. Information on perceived non-auditory health problems was obtained with an interviewer semi-structured questionnaire from consenting residents. Data were analyzed using descriptive statistics, ANOVA and T-test at 5% level of significance. The highest mean noise level 83.6±7.5dB was recorded between 5-8am at IWC. Mean noise levels (69. l±9.2dB) at the 12 religious centers were above WHO guideline limits for noise exposure (55dB) in residential environments. Most of the participants (42.8%) had sleep disturbance and 28.1% were highly annoyed as a result of religious noise. Other non-auditory health problems were loss of concentration (17.5%), speech interference (12.8%) and aggressiveness (12.5%). Residents living contiguous to religious houses are highly vulnerable to non-auditory health effects due to their exposure to excessive noise. Health education to the religious bodies on the adverse effects of excessive noise in the residential environment is advocated.